Neural Correlates of Cross-domain Affective Priming - Zhang, Qin (2010)
The affective priming effect has mostly been studied using reaction time measures; however, the neural bases of affective priming are not well established. To understand the neural correlates of cross-domain emotional stimuli presented rapidly, we obtained event-related potential (ERP) measures during an affective priming task using short SOA (stimulus onset asynchrony) conditions. Two sets of 480 picture-word pairs were presented at SOAs of either 150 ms or 250 ms between prime and target stimuli. Participants decided whether the valence of each target word was pleasant or unpleasant. Behavioral results from both SOA conditions were consistent with previous reports of affective priming, with longer RTs for incongruent than congruent pairs at SOAs of 150 ms (771 vs. 738 ms) and 250 ms (765 vs. 720 ms). ERP results revealed that the N400 effect (associated with incongruent pairs in affective processing) occurred at anterior scalp regions at an SOA of 150 ms, and this effect was only observed for negative target words across the scalp at an SOA of 250 ms. In contrast, late positive potentials (associated with attentional resource allocation) occurred across the scalp at an SOA of 250 ms. LPPs were only observed for positive target words at posterior parts of the brain at an SOA of 150 ms. Our finding of ERP signatures at very short SOAs provides the first neural evidence that affective pictures can exert an automatic influence on the evaluation of affective target words.